Political Experiment: The Effect of Conformity to Political Participaton On Beginner Voters - Dhien Amalia Putri; Lusy Asa Akhrani (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2019)
This research was aimed to determaine the effect of conformity to political participation on beginer voters. Political participation seen through eight componnents by Michel Bratton; interest in politics, discuss politics, belong voluntary organization, voted in last election, contacted goverment official, contacted elected official, contacted tradisional leader and protest or demonstrated (Bratton, 2009). The research method was an experimental design with two group post-test only design. The experiment was given to 42 Baghrul Maghfiroh’s beginer voters which consisting of two group, the experimental group and the control group. The instrument used political participation based on previous studies presented by Akhrani (2016). The result of independent sample t-test stating that there was diffrent conformity between experiment group and control group to political participation which significant value of 0,002 (p˂0,05).